Cluster-type lithium polysulfides regulator for high performance lithium-sulfur batteries. (20th January 2023) - Wang, Zhihua; You, Yingying; Cai, Yingying; Ni, Junze; Liu, Yilin; Zhang, Hanping
Highlights: 1 The strategy of modifying lithium polysulfides with cluster-type regulator to improve the performance of Li-S batteries was proposed for the first time. 2 The macromolecular LiPyS clusters have low solubility and thus can be confined to the cathode side. 3 LiPyS clusters can combine with LiPSs through double Li···S bonds to inhibit the "shuttle effect". 4 LiPyS clusters accelerate LiPSs redox kinetics based on frontier molecular orbital energy regulation strategy. Abstract: Lithium polysulfide intermediates suffer from serious "shuttle effect" and slow redox kinetics, resulting in limited rate performance, low discharge capacity and rapid capacity decay of lithium-sulfur (Li-S) batteries. Here, we propose a concept of cluster-type lithium polysulfides (LiPSs) regulator to address the above-mentioned problems. Dipyridyl disulfide (DpyDS) is introduced to be an electrolyte additive to form low solubility macromolecular lithium pyridine-2-thiolate (LiPyS) clusters in electrolyte by in-situ lithiation and Li bond network. The LiPyS monomer in the clusters form complexes (LiPyS-LiPSs) with LiPSs through bi-directional Li···S bonds, so as to restrict LiPSs to the clusters on the cathode side, preventing the parasitic reaction between LiPSs and Li metal. At the same time, LiPyS-LiPSs have higher HOMO energy levels and lower LUMO energy levels than that of single LiPSs. As a result, LiPSs can achieve an enhanced redox activity, and the Li-S battery regulated with DpyDS provides a capacity as high as 900 mA h g   −   1 at 2 C rate. Graphical abstract: Image, graphical abstract